Study on thermodynamic equivalent performance of fully ceramic microencapsulated fuel based on representative volume element model - Yin, Chunyu; Xiao, Zhong; Zhang, Kun; Cao, Peng; Tang, Changbing; He, Liang; Liu, Shichao (Frontiers in Energy Research, 2024)
Fully ceramic microencapsulated (FCM) fuel is a five-layer intercalation system material consisting of a UO2 core, a sparse pyrolytic carbon layer (Buffer), an inner dense pyrolytic carbon layer (IPyC), an outer dense pyrolytic carbon layer (OPyC), and a silicon carbide matrix (SiC). At first, this paper researched the thermodynamic models of the materials, including heat conduction coefficient, Young's modulus, thermal expansion coefficient, etc. Then DIGIMAT, the finite element software, was used to establish the equivalent volume element (RVE) for the equivalent analysis of the thermodynamic properties of the FCM fuel pellet. Finally, the thermodynamic equivalent performance model of FCM fuel was obtained by multi-factor fitting analysis. The results show that among these thermodynamic properties of FCM fuel pellets, the Young's modulus, thermal expansion coefficient and plastic performance are mainly affected by temperature, fast neutron fluence, and UO2 volume fraction; the specific heat capacity is mainly affected by UO2 volume fraction and temperature; the heat conduction coefficient is mainly affected by temperature and UO2 volume fraction. The thermal conductivity is mainly affected by temperature, burnup and UO2 volume fraction. In this study, the equivalent models obtained through the fitting analysis of RVE model parameters can well describe the thermodynamic behavior of FCM fuel particles.